Critically ill patients' intensive care unit experiences in a public sector academic hospital - Sitwala, Lilian Jere (My University, 2016)
Critically ill patients’ experiences are an important aspect of quality of care in the Intensive Care Unit (ICU) and have been a consistent theme in the last four decades. Intensive Care therapy has been associated with physical and psychological problems that may affect patient’s recovery from illness. Studies seem to indicate many patients recall ICU experiences in vivid details and frequently complain of fear, anxiety and pain. Now that the trend in sedation practices in Intensive Care has changed there are serious concerns that patients recalling memories of their experiences may be on the increase. The aim of this study was to describe critically ill patient’s experiences of their Intensive Care Unit experience, with the intention of making recommendations for clinical practice and education of intensive care nurses. A non-experimental, descriptive study was utilised in this study and non-probability sampling technique was employed to select patients. The setting for the study was a public sector academic institution, in South Africa. The sample size comprised of 80 (n=80), participants were selected from five (5) ICUs in a period of three (3) months. Purposive sampling was utilised and data was collected by a means of an Intensive Care Experience Questionnaire (ICEQ) developed by Rattray, Johnston and Wildsmith (2004). The questionnaire includes 24 items that assess four domains of ICU experience, these are awareness of surroundings (nine items), frightening experiences (six items), recall of experience (five items) and satisfaction with care (four items). Data was collected from patients in the general wards 24 to 48 hours after discharge from ICU. Data analysis using descriptive and inferential statistics was utilised to investigate patients experience in ICU. Statistical assistance was sought from the Medical Research Council (MRC). An independent t-test was used to test the significance difference and Analysis of Variances (ANOVA) was used to determine the difference between the groups and finally Post hoc test (Turkey HSD test) was developed to determine the location of differences in the groups. Post hoc comparison using turkey HSD test indicate there was a significant difference at p<0.05 level in frightened experience between age group 20-39 and 60-79. F (2, 80) = 4.949, p =0.010. The results indicate that most of the time majority (81.3%) of the participants felt safe and that care was as good as it could have been (75%) in the ICU. Majority (73.8%) of the participants remembered being with their relatives and recognised them. More than half (55%) seemed to be pain most of the time and had no recollections of ICU.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfillment of the requirements for the degree of Master of Science in Nursing Johannesburg, 2015